Predicting Stiffness Asphalt Natural Rubber Latex Modulus Value Using Multiple Linear Regression Analysis - Yudian Budi Krishna; Ramadhani; Hendrik Jimmyanto (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Every year, population growth increases, which causes a rise in the number of drivers. The road may become damaged as a result of this condition, necessitating repairs. Deformation and cracks in the pavement structure are the main contributors to damaged road conditions. Using natural rubber materials, such as natural rubber latex, is one of the modified asphalt methods that can solve this issue. The stiffness modulus is the asphalt's reaction to a load applied to it; this reaction can be used to evaluate the asphalt's rheological characteristics. While there was only an equation describing the stiffness modulus of oil asphalt up until now, and no research on the stiffness modulus model of rubber asphalt, the suggested study examines the prediction of the stiffness modulus model of latex natural rubber asphalt. The factors taken into consideration are natural rubber latex content, penetration, and softening point. Multiple linear regression analysis has been performed on the data, and the model validation results show an average error of 3.28% with a data distribution that is similar to the linear line with an R2 value of 0.9917.